2017
DOI: 10.1016/j.neuropsychologia.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric and allocentric visuospatial working memory in premotor Huntington's disease: A double dissociation with caudate and hippocampal volumes

Abstract: Our brains represent spatial information in egocentric (self-based) or allocentric (landmark-based) coordinates. Rodent studies have demonstrated a critical role for the caudate in egocentric navigation and the hippocampus in allocentric navigation. We administered tests of egocentric and allocentric working memory to individuals with premotor Huntington’s disease (pmHD), which is associated with early caudate nucleus atrophy, and controls. Each test had 80 trials during which subjects were asked to remember 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
(91 reference statements)
3
19
0
Order By: Relevance
“…Regarding networks subserving cognitive functions, the ECN showed consistent alterations in manifest HD patients (Figure 2), which might be linked with working memory deficits, one aspect of cognition often impaired in HD (Dumas et al, 2012;Possin et al, 2017;You et al, 2014). Conversely, in pre-HD individuals, the ECN showed no connectivity changes.…”
Section: Functional Network Involved In Hdmentioning
confidence: 92%
“…Regarding networks subserving cognitive functions, the ECN showed consistent alterations in manifest HD patients (Figure 2), which might be linked with working memory deficits, one aspect of cognition often impaired in HD (Dumas et al, 2012;Possin et al, 2017;You et al, 2014). Conversely, in pre-HD individuals, the ECN showed no connectivity changes.…”
Section: Functional Network Involved In Hdmentioning
confidence: 92%
“…In relation to spatial memory, the hippocampus is a key structure that facilitates allocentric learning and memory, whereas the striatum supports egocentric-based learning. The interplay between the striatum and the hippocampus has been suggested to explain the nature of spatial memory impairments seen in different stages of HD (Ciamei and Morton, 2009;Possin et al, 2017;Voermans et al, 2004). Essentially, in premanifest and early stages, when striatal degeneration is well underway, the hippocampus, which is then less affected, is thought to compensate for the lost striatalmediated function.…”
Section: Summary Of the Literature Reviewedmentioning
confidence: 99%
“…A second study that examined the relationship between HD neuropathology and spatial memory by Possin et al. (2017) showed a double dissociation between caudate nucleus and hippocampal volumes in egocentric/allocentric spatial working memory in premanifest HD. Using Postle and D’Esposito (2003) spatial working memory tests, which require participants to represent locations relative to their own position (egocentric) or relative to a landmark (allocentric), Possin found that people with premanifest HD ( n = 14) were more impaired on the egocentric than the allocentric working memory test.…”
Section: Introductionmentioning
confidence: 99%